2018
DOI: 10.2174/1874210601812010811
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of S-PRG Filler-Containing Toothpaste in Inhibiting Demineralization of Human Tooth Surface

Abstract: Objectives:Using an established pH-cycling caries model, the authors evaluated the effectiveness of toothpastes containing Surface Pre-reacted Glass-ionomer filler (S-PRG) in preventing tooth surface demineralization.Materials and Methods:210 tooth blocks were randomly assigned to seven experimental groups (30 blocks/group): no treatment (A), and toothpaste containing either NaF (B), 0 wt% S-PRG (C), 1 wt% S-PRG (D), 5 wt% S-PRG (E), 20 wt% S-PRG (F) or 30 wt% S-PRG (G). Groups were subjected to 14-day deminer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
(47 reference statements)
0
22
0
1
Order By: Relevance
“…A pH-cycling caries model serves as a bridge to in vivo caries studies as they mirror clinical conditions, where demineralization and remineralization alternate constantly (i.e., pH cycling) and are only interrupted during the very short period of application of investigational products. 29 , 30 pH cycling models have long been developed and described in the literature over the years, and have been accepted and utilized in dental sciences and the industry as an appropriate alternative to animal testing, particularly for ionic fluoride-based dentifrices. 33 – 35 One may argue that this model lack the cariogenic microbial biofilm that is a key factor in the caries process; however, the alternating feast and famine episodes that occurs in biofilm in the oral cavity is mimicked by alternating exposure of the samples to demineralization and remineralization solutions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A pH-cycling caries model serves as a bridge to in vivo caries studies as they mirror clinical conditions, where demineralization and remineralization alternate constantly (i.e., pH cycling) and are only interrupted during the very short period of application of investigational products. 29 , 30 pH cycling models have long been developed and described in the literature over the years, and have been accepted and utilized in dental sciences and the industry as an appropriate alternative to animal testing, particularly for ionic fluoride-based dentifrices. 33 – 35 One may argue that this model lack the cariogenic microbial biofilm that is a key factor in the caries process; however, the alternating feast and famine episodes that occurs in biofilm in the oral cavity is mimicked by alternating exposure of the samples to demineralization and remineralization solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Standard remineralization and demineralization solutions were prepared using previously published protocols. 28 30 The remineralization solution (artificial saliva) was composed of 3.8 ppm Mg 2+ (MgCl 2 ·6 H 2 O), 84.36 ppm PO 4 3− (K 2 HPO 4 /KH 2 PO 4 ) 50 ppm Ca 2+ (calcium lactate), 0.05 ppm fluoride, 0.625 g/L KCl, 0.4 g/L carboxymethylcellulose, and 2 g/L methyl-4-hydroxybenzoate, with the pH adjusted to 7.2 using 1 M KOH. The demineralizing solution (DS) served as an acid challenge simulating the acids generated in the dental plaque with intake of cariogenic meal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated the tooth-brushing pastes containing S-PRG fillers inhibited the demineralization of the enamel surface, which is in line with the results of the present study. Amaechi et al investigated the effect of S-PRG filler-containing toothpaste in various contents of the S-PRG filler on the inhibition of the demineralization of human the enamel surface, and showed that the toothpaste containing 20% and 30% S-PRG filler exhibited significantly less mineral loss than that containing 1% S-PRG filler 19) . The results of their study are similar to those of our study, although the procedures of application of toothpaste were different.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, Si, F, B, and Sr ions may contribute to increase the acid resistance of the dental surface due to their re-mineralization effect. Several studies have investigated the effects of toothpaste containing S-PRG fillers on the characteristics of tooth substance, and their results demonstrated the effectiveness of S-PRG fillers [18][19][20][21] . A few studies examined the effects of polishing with the MP on the acid resistance of the enamel surface; however, the available information is not enough 21) .…”
Section: Introductionmentioning
confidence: 99%